Compact design of a polarization beam splitter based on silicon-on-insulator platform. (20th September 2018) - Butt, M A; Khonina, S N; Kazanskiy, N L
Abstract: In this paper, a compact design of a polarization beam splitter is proposed, based on the principle of a directional coupler. A bridge waveguide is placed between two conventional silicon waveguide directional couplers. The optimized length of the bridge waveguide is obtained at 11 µ m, where the directional coupler acts as a polarization beam splitter. As a result, maximum polarization extinction ratios of 20.32 dB and 15.4 dB are obtained for the TE- and TM-modes, respectively, at a 1536 nm wavelength.